Sales Growth as a Moderating Variable: The Effect of Capital Intensity and Financial Distress on Tax Aggressiveness - Nur Indah Ambarwati; Napisah (Magister Akuntansi Universitas Pancasila, 2025)
PurposeThis study aims to examine the effect of capital intensity and financial distress on tax aggressiveness, with sales growth as a moderating variable, in industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. MethodologyThis research employs a quantitative associative approach using secondary data obtained from the annual financial statements of industrial sector firms listed on the IDX. The sample consists of 14 companies selected through purposive sampling, resulting in 70 firm-year observations. Panel data regression and Moderated Regression Analysis (MRA) were applied using EViews 12. FindingsThe findings indicate that tax aggressiveness is strongly impacted negatively by financial difficulty but not significantly by capital intensity. Furthermore, neither the association between financial distress and tax aggressiveness nor the relationship between capital intensity and tax aggressiveness are moderated by sales growth. ImplicationThe findings provide practical implications for management, investors, and policymakers in understanding corporate tax behavior, particularly under financial distress conditions. OriginalityThis study contributes to the tax aggressiveness literature by incorporating sales growth as a moderating variable in the Indonesian industrial sector context.